Depth of array micro-holes with large aspect ratio in Al based cast alloy. (28th March 2018) - Jin, Meiling; Qu, Yingdong; Li, Rongde
Abstract: In order to study on the depth of array micro-holes on Al base cast alloy, micro-hole with depth of 50 mm and diameter of 0.55 mm are successfully prepared by using poor wetting between carbon and Al. Accordingly, the mold of depth is established, the results show that calculated depth of micro-hole is 53.22 mm, relative error is 6% compare with the actual measured depth, and the depth of hole exponentially increases with the increasing of distance between two micro-holes. Surface tension and metallostatic pressure of metal molten are mainly affecting factors for depth of micro-holes.